Discovery and formal description of the female of Microphotina Beier, 1935 (Mantodea: Photinaidae), with an updated key to species and remarks on the role of Citizen Science in advancing Mantodea biodiversity studies - Rivera, Julio; Hausherr, Nicolas; Lanna, Leonardo Moutinho (Zootaxa, 2025)
French Guiana (FG) is renowned as one of the most extensively studied and recognized Neotropical regions for Mantodea. Despite comprehensive historical and contemporary collections, several taxa remain known from only one sex. This is the case for the females of Microphotina Beier, 1935 (Photinaidae, Microphotinini), whose elusiveness has prevented full characterization of this little-known lineage of foliage-dwelling praying mantises. In this study, we report and describe the female of Microphotina viridescens (Chopard, 1912), discovered in FG through citizen science efforts. We detail critical diagnostic features to recognize the female of M. viridescens and distinguish it from those of Chromatophotina Rivera, 2010, while reinterpreting wing and genital traits of males to enhance its recognition. The egg case is also described for the first time and compared with those of Chromatophotina awajun Rivera, 2010 and other closely related taxa. We complement taxonomy with general observations on the life history of M. viridescens, reporting habitat preferences, cryptic strategy, parental care, and aspects of its postembryonic development. Taxonomic and systematic considerations are provided along with an updated identification key to Microphotina spp. based on males. Finally, we briefly discuss the pivotal role that citizen science can play in advancing praying mantis biodiversity research.